Low FODMAP Diet and Probiotics in Irritable Bowel Syndrome: A Systematic Review With Network Meta-analysis - Xie, Chao-Rong; Tang, Bin; Shi, Yun-Zhou; Peng, Wen-Yan; Ye, Kun; Tao, Qing-Feng; Yu, Shu-Guang; Zheng, Hui; Chen, Min (Frontiers in Pharmacology, 2022)
Background: Probiotics and low fermentable oligosaccharides, disaccharides, monosaccharides, and polyols (FODMAPs) diet are two commonly used management approaches for patients with irritable bowel syndrome (IBS). We aimed to evaluate the most effective combinations and components among differential probiotics or low FODMAPs diet through component network meta-analysis (NMA). Methods: We searched Embase, Ovid Medline, and Web of Science from inception to January 21, 2021. Randomized controlled trials (RCTs) examining the efficacy of probiotics and low FODMAPs diet for IBS were included, with placebo, sham diet, or conventional treatments as controls. Binary outcomes were compared among treatments using the relative ratio (RR). A minimally contextualized framework recommended by the GRADE group was used to evaluate the certainty of evidence. The primary efficacy outcome was the relief of global IBS symptoms, and the secondary efficacy outcome was the reduction in IBS symptom scores or abdominal pain scores. Key Results: We included 68 RCTs (n=7555) after screening 1939 articles. Eight RCTs were classified as low risk of bias. Standard network meta-analysis (NMA) showed that Lactobacillus (RR 1.75, 95% CI 1.22 to 2.50) and Bifidobacterium (RR 1.77, 95% CI 1.01 to 3.10) were the most effective for the primary efficacy outcome (high certainty evidence); component NMA showed that Bacillus (RR 5.67, 95% CI 1.86 to 17.22, p=0.002) and Lactobacillus (RR 1.43, 95% CI 1.06 to 1.91, p=0.018) were among the most effective components. Conclusions: Lactobacillus was the most effective component for the relief of IBS symptoms; Bifidobacterium and Bacillus were possibly effective and need further verification.